Potential Value of Expiratory CT in Quantitative Assessment of Pulmonary Vessels in COPD - Cao, Xianxian; Gao, Xiaoyan; Yu, Nan; Shi, Meijuan; Wei, Xia; Huang, Xiaoqi; Xu, Shudi; Pu, Jiantao; Jin, Chenwang; Guo, Youmin (Frontiers in Medicine, 2021)
Objective: To investigate the associations between intrapulmonary vascular volume (IPVV) depicted on inspiratory and expiratory CT scans and disease severity in COPD patients, and to determine which CT parameters can be used to predict IPVV. Methods: We retrospectively collected 89 CT examinations acquired on COPD patients from an available database. All subjects underwent both inspiratory and expiratory CT scans. We quantified the IPVV, airway wall thickness (WT), the percentage of the airway wall area (WA%), and the extent of emphysema (LAA%−950) using an available pulmonary image analysis tool. The underlying relationship between IPVV and COPD severity, which was defined as mild COPD (GOLD stage I and II) and severe COPD (GOLD stage III and IV), was analyzed using the Student's t-test (or Mann-Whitney U-test). The correlations of IPVV with pulmonary function tests (PFTs), LAA%−950, and airway parameters for the third to sixth generation bronchus were analyzed using the Pearson or Spearman's rank correlation coefficients and multiple stepwise regression. Results: In the subgroup with only inspiratory examinations, the correlation coefficients between IPVV and PFT measures were −0.215 −0.292 (p < 0.05), the correlation coefficients between IPVV and WT3−6 were 0.233 0.557 (p < 0.05), and the correlation coefficient between IPVV and LAA%−950 were 0.238 0.409 (p < 0.05). In the subgroup with only expiratory scan, the correlation coefficients between IPVV and PFT measures were −0.238 −0.360 (p < 0.05), the correlation coefficients between IPVV and WT3−6 were 0.260 0.566 (p < 0.05), and the correlation coefficient between IPVV and LAA%−950 were 0.241 0.362 (p < 0.05). The multiple stepwise regression analyses demonstrated that WT were independently associated with IPVV (P < 0.05). Conclusion: The expiratory CT scans can provide a more accurate assessment of COPD than the inspiratory CT scans, and the airway wall thickness maybe an independent predictor of pulmonary vascular alteration in patients with COPD.